Integration of Character Education in Social Studies Learning - Raudah Devi Ekasari; Nurkhairina Nurkhairina (Universitas Pendidikan Indonesia (UPI), 2021)
This study aims to find out about the integration of character education in social studies learning, in the process carried out in integrating character education, which can increase understanding of the values of noble character education which includes several values including religious values, Pancasila values, cultural values, and national education goals. The research method used in this study is qualitative research method with the type of library research. Meanwhile, the data collection process in this study was carried out by reviewing library sources or documents considered relevant in this study and exploring several journals and books (both electronic and printed). Then the findings in this study are that education is basically a conscious effort to develop the potential of students optimally. character education, namely; shaping the child's personality, so that he becomes a good human being, a good citizen, so that he is able to anticipate the symptoms of a moral crisis and play a role in the development of the younger generation. Then social studies education is a subject that examines social life whose material is based on studies of history, geography, economics, sociology, anthropology, and state administration. Through social studies learning, character education values can be included by integrating the material in the social studies learning. Then social studies education is a subject that examines social life whose material is based on studies of history, geography, economics, sociology, anthropology, and state administration. Through social studies learning, character education values can be included by integrating the material in the social studies learning. Then social studies education is a subject that examines social life whose material is based on studies of history, geography, economics, sociology, anthropology and state administration. Through social studies learning, character education values can be included by integrating the lesson in the social studies learning.